Inhibitive Action of Argan Press Cake Extract on the Corrosion of Steel in Acidic Media - Afia,L. (2012)
The inhibitive action of the Argan press cake extract (ACE) against corrosion of C38 steel in a 1 M HCl solution was investigated using potentiodynamic polarization curves, electrochemical impedance spectroscopy (EIS) and weight loss measurements. The inhibition efficiency increases with increasing extract concentration and decreases with temperature. The kinetic parameters (activation energy, pre-exponential factor, enthalpy of activation and entropy of activation) were calculated and discussed. The Argan press cake extract acted as a mixed-type inhibitor with predominant cathodic effectiveness. The Nyquist plots showed that on increasing ACE concentration, increases charge transfer resistance and decreases double layer capacitance. The adsorption of components of the the Argan press cake extract (ACE) on the surface of the C38 steel follows the Langmuir adsorption isotherm. E (%) values obtained from various methods used are in good agreement.